The Cambridge Companion to Early Modern Philosophy - Rutherford, Donald (Cambridge Cambridge University Press, 2006)
The Cambridge Companion to Early Modern Philosophy is a comprehensive introduction to the central topics and changing shape of philosophical inquiry in the seventeenth and eighteenth centuries. It explores one of the most innovative periods in the history of Western philosophy, extending from Montaigne, Bacon and Descartes through Hume and Kant. During this period, philosophers initiated and responded to major intellectual developments in natural science, religion, and politics, transforming in the process concepts and doctrines inherited from ancient and medieval philosophy. In this Companion, leading specialists examine early modern treatments of the methodological and conceptual foundations of natural science, metaphysics, philosophy of mind, logic and language, moral and political philosophy, and theology. A final chapter looks forward to the philosophy of the Enlightenment. This will be an invaluable guide for all who are interested in the philosophical thought of the early modern period
Keywords: 17th Century (1601-1700); 18th Century (1701-1800); Philosophy